Features of intra landscape differentiation of invertebrates of circus ecotone on the example of the Sofia ridge - Victoria Victorovna Koneva (Наука. Инновации. Технологии, 2022)
The experience of studying mountain lands in transitional ecotone zone of upper forest border of West Caucasus coniferous forests to subalpine plains let to realize quality-quantity evaluation of main elements of Hortobionts habitat, but to turn out on creating integral logic-mathematical model of phase habitat.